Scope, scale, and dose of the world's largest school-based mental health programs - Murphy, JM; Abel, MR; Hoover, S; Jellinek, M; Fazel, M (Lippincott, Williams & Wilkins, 2017)
Untreated mental health problems are among the most disabling, persistent, and costly health conditions. Because they often begin in childhood and continue into adulthood, there has been growing interest in preventive mental health programs for children. In recent years, several such programs have been implemented at regional, state, or national scale, and although many experimental studies have documented positive outcomes of individual programs, this article represents the first attempt to systematically compare the largest programs in terms of scope, scale, and dose. The school-based mental health programs discussed in this review appear to have reached more than 27 million children over the last decade, and many of these programs have collected systematic outcomes data. The role that such programs can play in low- and middle-income countries (LMICs) is a secondary focus of this article. Until recently, wide-scaled, preventive, mental health interventions for children have been studied almost exclusively in high-income countries even though around 80% of the global population of children reside in LMICs. Since a number of programs are now operating on a large scale in LMICs, it has become possible to consider child mental health programs from a more global perspective. With both the increasing diversity of countries represented and the growing scale of programs, data sets of increasing quality and size are opening up new opportunities to assess the degree to which preventive interventions for child mental health, delivered at scale, can play a role in improving health and other life outcomes.